Town’s Symbol in the Mind of its Residents as a Determinant of a Concept of ‘Capitalness’: The Cases of Kasimov and Myshkin - B. A. Barabash (Сравнительная политика, 2015)
The article concerns comparative analysis of the spread of the term ‘capitalness’ in two small Russian towns.